Tree community structure and carbon stock of a secondary forest in Universiti Teknologi Malaysia campus - Md. Isa, Nurun Nadhirah (2018)
Recently, anthropogenic activities such as forest logging, plantation and urban development have influenced the growth of secondary forests throughout the tropics. In Universiti Teknologi Malaysia (UTM), secondary forest has emerged after the removal of rubber plantation, which has led this study to identify secondary forest composition, estimate the amount of carbon stock from the above-ground biomass (AGB), below-ground biomass (BGB) and soil organic carbon, and identify tree distribution based on soil, chemical and physical properties. In this study, 200 plots with an area of 100 m2 each were established within UTM‘s secondary forest. The diameter at breast height (DBH), the tree height, coordinates for each tree species and soil samples were collected. Top-soil samples in 50 selected plots were collected and analysed for texture, pH, base cation and available nutrients, including Mg, P and K. Shannon diversity index was applied in measuring species diversity. Then, a satellite image acquisition from Pleiades and spectral radiometer data collection were carried out to compile spectral data of fresh leaves from 25 species. For species composition, a total of 1,917 tree stands, comprising 25 species from 17 genera and 15 families were enumerated in all the study plots. Euphorbiaceae is the largest family with a total basal area (BA) of 29.6 m2/ha which contributes to the high density in UTM secondary forest. The Shannon Diversity Index in UTM secondary forest was 2.248 (Hmax= 3.219) which is lower than for primary forest. The total tree biomass was 84.6 t/ha, which was composed of AGB of 61.3 t/ha and BGB of 23.3 t/ha. The amount of carbon stock in this forest was 40.1 t/ha for AGB (28.8 t/ha), BGB (11 t/ha), and in the soil (0.79 t/ha). The total amount of soil organic carbon in UTM was 37.39 t/ha. Finally, ordinations by using Canonical Correspondence Analysis (CCA) indicated that soil, chemical and physical factors had no relationship with vegetation distribution. According to supervised classification for carbon stock estimation, the total carbon stock from 173.80 hectares of secondary forest in UTM amounted to 11,731.5 tonnes of carbon. Therefore, the secondary forest in UTM should be conserved as a carbon reservoir.